IMPACT OF IMPROVED VARIETY ADOPTION ON FARM INCOME IN TOLON DISTRICT OF GHANA - Hajaratu Ahmed; Benjamin Tetteh Anang (Socio-Economics/Agribusiness Department, 2019)
This paper estimates the effect of improved maize variety adoption on farm income in the Tolon District of Ghana. The study covered the 2017/2018 farming season and involved 160 randomly selected maize farmers from four communities in the district. A regression with endogenous treatment effect model, which accounts for selection bias arising from both observable and unobservable factors was used to estimate the effect of improved maize variety adoption on farm income. The results indicate that men have lower probability of adoption while adoption increased with extension contact, access to fertilizer subsidy and cattle ownership but decreased with the cost of adoption. The results further indicate that adoption is significantly and positively related to farm income. Adoption of improved maize varieties increased gross farm income of maize farmers by GH¢852. Farm income also increased with farm size and cattle ownership but was lower for female farmers. Institutional factors such as provision of agricultural extension advisory services and subsidized fertilizer are essential to promote adoption of improved varieties; hence these services should be made readily available to farmers. Addressing the problem of inadequate extension staff and logistical challenges confronting extension workers are some of the pragmatic steps required to promote adoption of improved varieties in order to improve farm incomes. Furthermore, subsidized fertilizer should be made available to farmers on time and in the right quantities to enhance adoption and farm incomes, while farmers should be encouraged to rear livestock as this enhances both adoption and farm income.